Wild horse country - Diaz , Katacha; Casale, Paul; Galvin, Laura Gates; Pilchowski, Marcin D; Shriver, Chelsea (London Sound Prints, 2003)
A young foal is born into a pack of wild horses roaming the dry plains. Includes facts about the wild horse
Science (Animals)
Keywords: Animals